2013
DOI: 10.1590/s2317-17822013000500007
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the "An Object and Action Naming Battery" in Brazilian Portuguese

Abstract: The OANB may be used in adult Brazilian Portuguese native speakers. The group with higher education had higher scores; both groups had a higher proportion of "semantic errors" for verbs and nouns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…MoCA is suggested by the literature as the most sensitive screening test to detect cognitive changes in PD, because it assesses the executive functions that are predominantly affected by PD (7)(8) . We also conducted a brief language evaluation using semantic (9) , phonemic (10) and action (verbs) (11) verbal fluency, as well as an oral naming of action figures and objects using 60 images from the An Object and Action Naming Battery (OANB) (12,13) .…”
Section: Cognition and Language Evaluationmentioning
confidence: 99%
“…MoCA is suggested by the literature as the most sensitive screening test to detect cognitive changes in PD, because it assesses the executive functions that are predominantly affected by PD (7)(8) . We also conducted a brief language evaluation using semantic (9) , phonemic (10) and action (verbs) (11) verbal fluency, as well as an oral naming of action figures and objects using 60 images from the An Object and Action Naming Battery (OANB) (12,13) .…”
Section: Cognition and Language Evaluationmentioning
confidence: 99%
“…The recognition rates for the items confirmed that the target words were in the children's vocabulary, since accurate naming requires familiarity with the image or action presented. The process of visual naming occurs in three stages: (1) identification of the object in the visual representation; (2) access to the corresponding semantic representation, to allow for recognition, and (3) lexicalization, or activation of the phonological processes through which the name of the image is recovered and pronounced (23) . Lexical development is related to the acquisition of the phonological inventory, and there is a need for studies which show how lexical and phonological factors can influence speech production, and apply this information to the diagnosis and treatment of children with atypical phonological development (24) .…”
Section: Discussionmentioning
confidence: 99%
“…Bildbatteriet OANB, särskilt aktivitetsbilderna, har utvärderats och adapterats till olika språk och kulturer (Bogka et al 2003;Cuetos & Alija 2003;Schwitter, Laganaro, Boyer, Méot & Bonin 2004;Spezzano, Mansur & Radanovic 2013;Edmonds & Donovan 2014;Shao, Roelofs & Meyer 2014;Alyahya & Druks 2015;Nilipour, Bakhtiar, Momenian & Weekes 2017;Rami, Diouny, Yeou, Kissani 2022). En svensk version av OANB har också utarbetats genom flera delstudier (Andersson & Larsfelt 2013;Hellberg & Kroon 2014;Kristensson, Behrns & Saldert 2015;Torinsson & Åke 2017).…”
Section: Bakgrundunclassified